Aluminum powder / gallium nitrate lithium ion battery composite electrode material and preparation method thereof

By combining aluminum powder with gallium nitrate and using gallium metal particles to etch the oxide film on the surface of the aluminum powder, the problem of low lithium storage capacity of aluminum powder is solved, and an efficient and safe lithium-ion battery negative electrode material is achieved.

CN119786540APending Publication Date: 2025-04-08HUBEI NANGUI ALUMINUM GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411905460.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When aluminum powder is used as the negative electrode material of lithium-ion batteries, the presence of an oxide film on the surface inhibits its reactivity, resulting in a low lithium storage capacity.

Method used

By compounding aluminum powder with gallium nitrate, the oxide film on the surface of the aluminum powder is etched using gallium metal particles generated by gallium nitrate in the electrochemical reaction, thereby enhancing the reactivity and lithium storage capacity of the aluminum powder.

Benefits of technology

It significantly improves the lithium storage capacity of aluminum powder, ensures the safety and efficiency of the battery, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786540A_ABST
    Figure CN119786540A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum powder / gallium nitrate lithium ion battery composite electrode material and a preparation method thereof. The preparation method comprises the following specific steps: weighing aluminum powder (1-3 m), acetylene black, gallium nitrate and a polyvinylidene fluoride solution (PVDF is dissolved in N-methyl pyrrolidone, and the mass concentration is 0.01-0.03 g / mL) in proportion, and uniformly mixing the materials in a small glass bottle with the volume of 10 mL according to a certain method; and uniformly coating a copper foil fixed by a coating machine with the slurry by using a glass rod, transferring the copper foil to a vacuum oven, drying for 7-10 hours at the temperature of 60-80 DEG C under the pressure of-1-0.1 MPa, and cutting the copper foil into wafers with the diameter of 14 mm for later use by using a slicing machine after drying is completed, thereby obtaining the electrode plate loaded with the aluminum powder and gallium nitrate composite material. The prepared aluminum powder / gallium nitrate composite material has high reaction activity and high lithium storage capacity (the capacity provided by the aluminum powder is about 400 mAh g <-1 > and 0.2 A g <-1 >), the important application value is shown, the preparation method is simple, and the aluminum powder / gallium nitrate composite material has the important application value in lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a novel composite negative electrode material for lithium ion batteries, in particular to a design of composite aluminum powder and gallium nitrate as a lithium ion negative electrode material, belonging to the field of electrochemical energy. Background Art

[0002] In order to cope with global warming and my country's high dependence on foreign traditional fossil energy, my country has proposed dual carbon goals. In this context, my country's energy use is gradually transforming from fossil energy to clean energy, which can reduce dependence on imported fossil energy and enhance energy self-sufficiency. However, how to achieve efficient use of clean energy has always been a difficult problem, and people's attention has gradually focused on high-performance energy storage devices.

[0003] As one of the members of high-performance energy storage devices, lithium-ion batteries are indispensable in everything from flashlights and mobile phones to electric vehicles and distributed energy storage power stations. With the development of society, people have put forward higher and higher requirements on the performance of lithium-ion batteries. For lithium-ion batteries, the research and development of negative electrode materials is directly related to the performance and application of lithium-ion batteries. At present, carbon materials are widely used in negative electrode materials, and their theoretical capacity is only 372 mAh g -1 , and it is easy to produce dendrites and other problems, which may lead to battery safety hazards. Therefore, it is particularly important to develop high-capacity negative electrode materials with a suitable platform to meet the needs of modern lithium-ion batteries.

[0004] Aluminum is a member of the alloy negative electrode materials for lithium-ion batteries. It is abundant in the earth's crust. When aluminum is used as the negative electrode of a lithium-ion battery, it forms a LiAl alloy during discharge, with a platform of about 0.2 V and a charging platform of about 0.4 V. The theoretical capacity is 993 mAh g -1 . Since the alloying potential is relatively high, dendrites will not be produced like the electrochemical reaction of carbon material intercalation of lithium. Unfortunately, the aluminum negative electrode itself is highly active and an oxide film will form on the surface in the air, which will hinder the Li in the electrolyte. +Reacts with active Al. In recent years, studies have found that salt materials can also be used as electrode materials for lithium-ion batteries. Among them, nitrates have a higher capacity as negative electrode materials for lithium-ion batteries. At the same time, the N-containing solid electrolyte interface layer (SEI) formed by the partial decomposition of nitrates is beneficial to improving the stability of the electrode. Our previous explorations found that gallium nitrate, as a negative electrode material for lithium-ion batteries, shows a capacity far higher than that of ordinary salts and gallium-based negative electrode materials. The main reason lies in its special conversion / alloying composite reaction mechanism: gallium nitrate as a negative electrode material can form LiNO3 and gallium elements during the discharge process, and gallium further forms an alloy with lithium in the subsequent lithium insertion process. The in-situ formed gallium has high reactivity and has a certain etching effect on ordinary metals and metals containing oxide films.

[0005] Based on the above background, in order to solve the problem that the oxide film on the surface of aluminum powder particles inhibits the reaction activity, this patent attempts to use the highly active gallium formed in situ to etch the oxide film on the surface of aluminum powder particles, thereby increasing the capacity of aluminum powder particles. The aluminum powder and gallium nitrate composite material prepared in this patent has a high and stable capacity (the capacity provided by aluminum powder is about 400 mAh g -1 , 0.2 A g -1 ), showing important application value. Summary of the invention

[0006] A method for preparing an aluminum powder and gallium nitrate composite lithium-ion battery electrode material, wherein gallium metal particles generated in an electrochemical reaction of gallium nitrate are used to etch aluminum powder, so that the lithium storage capacity of the aluminum negative electrode is significantly improved. The steps for preparing the composite material are as follows: (1) Add gallium nitrate to a certain amount of polyvinylidene fluoride (PVDF) solution, and stir the above materials for a certain period of time to dissolve the gallium nitrate.

[0007] (2) The mixed material obtained in step (1) was then mixed with aluminum powder (1-3 μm), acetylene black, and supplemented with solvent N-methylpyrrolidone (NMP), and stirred overnight.

[0008] (3) The slurry obtained in step (2) is evenly coated on a copper foil, and placed in a vacuum drying oven for drying to obtain an electrode sheet loaded with a composite electrode material of aluminum powder and gallium nitrate.

[0009] The mass concentration of the PVDF solution is 0.01-0.03 g / mL.

[0010] The ratio of the amount of gallium nitrate added to the amount of PVDF added is 0.5-6:1, and the stirring time is 1-2 hours.

[0011] The aluminum powder has a diameter of 1-3 μm and a purity of 99.9%. Due to exposure to air, an oxide film is formed on the surface.

[0012] The mass ratio of the aluminum powder, gallium nitrate, acetylene black and polyvinylidene fluoride (PVDF) is 0.5-3:0.5-3:1-3:1. The order is to add aluminum powder first, wherein the diameter of the aluminum powder is 1-3 μm. Due to contact with the air, there will be an oxide film on the surface. Then, acetylene black is added while NMP is dripped in. The final mass concentration of the mixture is 0.05-0.2 g / mL.

[0013] The mixture is stirred for 10-12 hours.

[0014] The surface mass of the active composite material participating in the electrochemical reaction on the electrode sheet is 0.2-0.4 mg / cm 2 .

[0015] The electrode sheet is vacuum dried under -1~0.1MPa and 60-80°C for 7-10 hours. After drying, it is cut into discs with a diameter of 14 mm using a slicer for standby use.

[0016] Because aluminum materials themselves are highly reactive, an oxide film will form on their surface when stored in air, which will prevent the electrolyte from reacting with aluminum as an electrode material, resulting in lower reactivity of aluminum materials and lower lithium storage performance. This patent is specifically for aluminum materials, and aluminum powder is preferred as the negative electrode material, which is compounded with gallium nitrate. Gallium metal particles generated by gallium nitrate during the electrochemical reaction process are used to etch the oxide film on the surface of the aluminum powder (2Ga+Al2O3=Ga2O3+2Al), so that the aluminum inside the aluminum powder contacts the electrolyte, and produces a synergistic effect with aluminum during the electrochemical reaction, thereby increasing the capacity of the aluminum negative electrode.

[0017] The method for preparing the aluminum powder / gallium nitrate composite material of the present invention has the following obvious advantages: The lithium storage capacity is high, the lithium storage point is low and relatively safe. The material source is simple, easy to obtain, and the cost is low, which is conducive to its practical application. The capacity contributed by the aluminum negative electrode is calculated to be 380-400 mAh g -1 This allows the aluminum powder, which originally has a low cycle capacity, to play its role as the negative electrode. The synthesis method is simple and easy to repeat. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 .XRD of the composite material of Example 1.

[0019] Figure 2 Example 1 CV curve of gallium nitrate (a) and the third cycle CV curve of pure aluminum powder and composite material Figure 3 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 1.

[0020] Figure 4 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 2.

[0021] Figure 5 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 3.

[0022] Figure 6 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 4.

[0023] Figure 7 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 5.

[0024] Figure 8 .The first charge and discharge curve (a) and cycle performance diagram (b) of Example 6. DETAILED DESCRIPTION

[0025] Example 1 Take aluminum powder (1-3μm): gallium nitrate: acetylene black: polyvinylidene fluoride (PVDF) in a mass ratio of 3:3:3:1, where PVDF is dissolved in NMP (N-methylpyrrolidone) as a solvent, the concentration of PVDF solution is 0.02 g / mL, and the amount added is 1 mL. The preparation environment is a 10 mL glass vial, and the order of addition is PVDF solution, gallium nitrate, stirring for 1-2 hours, and after the gallium nitrate is dissolved, aluminum powder is added, and then acetylene black is added while dripping 3 mL of N-methylpyrrolidone (NMP), and then stirred for 10 hours to make the slurry formed by the above materials evenly mixed, and the final mixture mass concentration is 0.1 g / mL. Use a coating machine to fix the copper foil flatly, and then use a glass rod to evenly coat the stirred slurry on the copper foil, and then transfer the copper foil coated with the material to a vacuum drying oven to evaporate N-methylpyrrolidone. The vacuum drying conditions are -1~0.1MPa, 60-80℃ drying for 9 hours, and after drying, it is cut into 14 mm diameter discs with a slicer for use. The surface mass of the active composite material participating in the electrochemical reaction coated on the electrode sheet is 0.3 mg / cm 2 .

[0026] In another vial, add aluminum powder and gallium nitrate in the same proportion as in the above step, without adding acetylene black and PVDF solution, mix well and vacuum dry to obtain a composite material of aluminum powder and gallium nitrate. The XRD characteristics of the material are as follows: Figure 1 As shown, its main components can correspond to the standard card PDF#04-0787 of Al, and there is no diffraction peak of gallium nitrate because it is transformed into an amorphous state.

[0027] Assemble the half-cell, use the metal lithium sheet with a diameter of 14 mm as the counter electrode, the diaphragm material is Celgard 2400 polypropylene microporous membrane, and the electrolyte is LiPF6 solution dissolved in EC:DMC:DEC (volume ratio of 1:1:1). The assembly was carried out in a glove box filled with argon (the volume fractions of water and oxygen were both less than one millionth), and the battery model was 2025. The assembled battery was sealed with a sealing machine at a pressure of 50 MPa, and then left to stand for 8-10 h. The charge and discharge test was carried out on Land CT2001, with a test voltage range of 3-0.01 V and a current density of 0.02 A g -1 Pure gallium nitrate was prepared into an electrode and a battery was prepared according to the above method. The first cycle cyclic voltammetry curve was measured as follows: Figure 2 As shown in (a), compared with the composite material, both materials have a reduction peak at 1.42 V. The corresponding electrochemical reaction is that Ga(NO3)3 is reduced to Ga metal particles. The reduced Ga single particles have an etching effect on the surface of aluminum powder. Figure 2 (b) is the third cycle cyclic voltammetry curve of pure aluminum powder and composite material. It can be seen that the composite material has an obvious oxidation peak at around 0.49V, while pure aluminum powder has almost no peak, indicating that its electrochemical reaction activity is low. It can be seen that adding gallium nitrate can improve the electrochemical reaction activity of aluminum powder. Figure 3 As shown in Figure 2, the composite electrode has obvious discharge and charge platforms near 0.25 and 0.38 V. -1 Under the conditions, the first discharge capacity is 2592 mAh g -1 , charging capacity is 1461 mAh g -1 The initial coulombic efficiency is 56.37%. The charge-discharge curve and capacity correspond to the Al negative electrode in the subsequent example, indicating that the Al in the prepared electrode has lithium storage activity. After 120 stable cycles, the capacity remains at 895 mAh g -1 According to the cyclically stable capacity of pure aluminum powder (1-3 m) in Example 2 and the cyclically stable capacity of gallium nitrate in Example 3, the cyclically stable capacity of the material in Example 1 minus the cyclically stable capacity of gallium nitrate in Example 3 multiplied by the proportion of gallium nitrate in Example 1, it can be concluded that the capacity contributed by aluminum powder (1-3 m) in Example 1 is 392 mAh g -1 , the electrochemical performance is good.

[0028] Example 2 Pure aluminum powder (1-3 μm) was used as the electrode material, and was mixed with acetylene black and polyvinylidene fluoride in a weight ratio of 6:3:1, wherein PVDF was dissolved in NMP (N-methylpyrrolidone) as a solvent, the concentration of the PVDF solution was 0.03 g / mL, and the amount added was 1 mL; 3 mL of N-methylpyrrolidone was added as a mixing environment to make a slurry, which was coated on a copper foil, wherein the stirring step and the drying conditions were the same as those in Example 1. The corresponding electrochemical properties of the material are as follows Figure 4 As shown, at 0.2 A g -1 The first discharge capacity under the condition is 889 mAh g -1 , charging capacity is 593 mAh g -1 The first coulombic efficiency was 66.8%, but after 20 cycles, the capacity dropped to 200 mAh g -1 Comparing the nano aluminum powder (200 nm) of Example 5 with the large diameter aluminum powder (7-8 μm) of Example 6, the first coulomb efficiency is higher, so the aluminum powder of this diameter is selected as the research object of Example 1.

[0029] Example 3 Pure gallium nitrate was used as the electrode material, mixed with acetylene black and PVDF in a weight ratio of 6:3:1, wherein PVDF was dissolved in NMP (N-methylpyrrolidone) as a solvent, the PVDF solution concentration was 0.03 g / mL, the amount added was 1 mL, and 3 mL of N-methylpyrrolidone was added as a mixing environment to make a slurry, which was coated on a copper foil, wherein the stirring step and the drying conditions were the same as those in Example 1. Figure 5 It can be seen that at 0.2 A g -1 Under the above conditions, the first discharge capacity of the material is 1985 mAh g -1 , charging capacity is 1109 mAh g -1 The first coulombic efficiency is 55.8%, and the capacity is stable at 1006 mAh g after 120 cycles. -1 . This indicates that the material has a higher capacity.

[0030] Example 4 Aluminum powder (7-8 μm): gallium nitrate: acetylene black: polyvinylidene fluoride (PVDF) was prepared in a mass ratio of 3:3:3:1, wherein PVDF was dissolved in NMP (N-methylpyrrolidone) as a solvent, the PVDF solution concentration was 0.03 g / mL, the amount added was 1 mL, and 3 mL of N-methylpyrrolidone was added as a mixing environment to prepare a slurry, which was then coated on a copper foil. The stirring and drying conditions were the same as those in Example 1, and an electrode sheet was prepared according to the method described in Example 1, and a battery was assembled. -1The first charge and discharge curves and cycle performance are shown in Figure 2. Figure 6 As shown in the figure, a lithium-aluminum alloy platform can appear, and the first charge and discharge capacity is 1665 mAh g -1 , 913 mAh g -1 The initial efficiency is 54.8%, and it remains at 782 mAh g after 120 cycles. -1 The capacity contributed by aluminum powder is calculated to be 282 mAh g -1 , which may be due to the large size of aluminum powder, and the aluminum inside cannot participate in the reaction.

[0031] Example 5 Pure aluminum powder (7-8 μm) was used as the electrode material, mixed with acetylene black and polyvinylidene fluoride in a weight ratio of 6:3:1, wherein PVDF was dissolved in NMP (N-methylpyrrolidone) as a solvent, the PVDF solution concentration was 0.03 g / mL, the addition amount was 1 mL, and 3 mL of N-methylpyrrolidone was added as a mixing environment to make a slurry, which was coated on a copper foil, wherein the stirring step and the drying conditions were the same as those in Example 1, and the electrode sheet was prepared according to the method described in Example 1, and the battery was assembled. -1 The first charge and discharge curves and cycle performance are shown in Figure 2. Figure 7 As shown in Figure 1, there is a platform of lithium-aluminum alloy. The first charge and discharge capacity is 606 mAh g -1 , 906 mAh g -1 The first efficiency is 65.5%, and after 20 cycles at 200 mA hg -1 Hereinafter, the first effect is lower than that of Example 2.

[0032] Example 6 Pure aluminum powder (200 nm) was used as the electrode material, mixed with acetylene black and polyvinylidene fluoride in a weight ratio of 6:3:1, wherein PVDF was dissolved in NMP (N-methylpyrrolidone) as a solvent, the PVDF solution concentration was 0.03 g / mL, the amount added was 1 mL, and 3 mL of N-methylpyrrolidone was added as a mixing environment to make a slurry, which was coated on a copper foil, wherein the stirring step and drying conditions were the same as those in Example 1, and the electrode sheet was prepared according to the method described in Example 1, and assembled into a battery. -1 The first charge and discharge curves and cycle performance are shown in Figure 2. Figure 8 As shown in Figure 1, there is a platform of lithium-aluminum alloy. The first charge and discharge capacity is 644 mAh g -1 、1012 mAh g -1The first effect is 63.7%. For nano-aluminum powder, its oxide film may be too thick and may not release the performance of aluminum powder when compounded with gallium nitrate.

Claims

1. A method for preparing a composite electrode material of aluminum powder and gallium nitrate lithium ion battery, characterized in that: The steps of preparing the composite material are as follows: (1) Add gallium nitrate to the polyvinylidene fluoride (PVDF) solution and stir to dissolve the gallium nitrate; (2) Add aluminum powder and acetylene black to the mixed material obtained in step (1), add solvent N-methylpyrrolidone (NMP), and stir overnight; (3) The slurry obtained in step (2) is evenly coated on a copper foil and vacuum dried to obtain an electrode sheet loaded with a composite electrode material of aluminum powder and gallium nitrate.

2. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: The PVDF solution in step (1) is an N-methylpyrrolidone solution of PVDF, and the concentration of the PVDF solution is 0.01-0.03 g / mL.

3. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: The ratio of the amount of gallium nitrate added to the amount of PVDF added in step (1) is 0.5-6:

1.

4. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: In step (2), the mass ratio of aluminum powder, gallium nitrate, acetylene black and PVDF is 0.5-3:0.5-3:1-3:1, the diameter of the aluminum powder is 1-3 μm, and the order is to add aluminum powder first, and then add acetylene black while dripping NMP.

5. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: The stirring time of step (2) is 10-12 hours.

6. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: The surface mass of the active composite material participating in the electrochemical reaction coated in step (3) is 0.2-0.4 mg / cm 2 .

7. The method for preparing the composite electrode material of aluminum powder and gallium nitrate lithium ion battery according to claim 1, characterized in that: The electrode sheet obtained in step (3) is dried under vacuum conditions of -1 to 0.1 MPa at 60 to 80° C. for 7 to 10 hours.

8. A negative electrode material for a lithium ion battery, characterized in that: The method is prepared by any one of claims 1 to 7.